Can Overgrazing Responses Be Disentangled by Above- and Below-Ground Traits? - Zhang, Hui; He, Qifang; Pandey, Shree Prakash; Jiang, Kai; Wang, Chen (Frontiers in Ecology and Evolution, 2021)
Understanding functional traits that capture species response to overgrazing can help optimize ecosystem functioning. However, most studies have ignored the effects of life-form on the response of above- and below-ground traits to overgrazing. Here, we determined whether the above- and below-ground traits respond similarly to overgrazing; and does the response of above- and below-ground traits to overgrazing vary between the species of annual vs perennial life-forms. We compared common grassland species between undisturbed and overgrazed meadows at four elevations (from 3000 to 3600 m), spanning an area of ~200 square kilometers on the Qinghai-Tibetan Plateau. We found overgrazing resulted in large removal of perennial species at all elevations, which forced perennial species to alter their above- and below-ground traits so that they could shift from resource conservation to resource acquisition to avoid overgrazing. In contrast, overgrazing promoted annual species at all elevation, thus annual species did not make any response to overgrazing. These findings bridge the gap in the literature for the influence of annual vs perennial life-forms on species-specific response at both above-, and below-ground levels during overgrazing. More important, these results can facilitate selecting species for sustainable ecosystem managements and restoration from overgrazing.